2020
DOI: 10.1186/s12870-020-02411-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of CYP450 and UGT supergene family members from the transcriptome of Aralia elata (Miq.) seem reveal candidate genes for triterpenoid saponin biosynthesis

Abstract: Background: Members of the cytochrome P450 (CYP450) and UDP-glycosyltransferase (UGT) gene superfamily have been shown to play essential roles in regulating secondary metabolite biosynthesis. However, the systematic identification of CYP450s and UGTs has not been reported in Aralia elata (Miq.) Seem, a highly valued medicinal plant. Results: In the present study, we conducted the RNA-sequencing (RNA-seq) analysis of the leaves, stems, and roots of A. elata, yielding 66,713 total unigenes. Following annotation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 54 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…Expression analysis showed that the obtained CYP450 genes maintain a high expression level during the differentiation of walnut exocarp, which would contribute to juglone accumulation. This result is similar to the secondary metabolite biosynthesis in plants such as Aconitum vilmorinianum (aconite) [ 60 ], Salvia miltiorrhiza (red sage) [ 61 ], Scutellaria baicalensis (Chinese skullcap) [ 62 ], and Aralia elata (angelica tree) [ 63 ]. Additionally, we identified the expanded CYP450 gene family from the genome assembly of the J. mandshurica , suggesting that they may specifically affect juglone biosynthesis.…”
Section: Discussionsupporting
confidence: 58%
“…Expression analysis showed that the obtained CYP450 genes maintain a high expression level during the differentiation of walnut exocarp, which would contribute to juglone accumulation. This result is similar to the secondary metabolite biosynthesis in plants such as Aconitum vilmorinianum (aconite) [ 60 ], Salvia miltiorrhiza (red sage) [ 61 ], Scutellaria baicalensis (Chinese skullcap) [ 62 ], and Aralia elata (angelica tree) [ 63 ]. Additionally, we identified the expanded CYP450 gene family from the genome assembly of the J. mandshurica , suggesting that they may specifically affect juglone biosynthesis.…”
Section: Discussionsupporting
confidence: 58%
“…In that work, the authors proposed a biogenetic pathway for celastrol in which hydroxyfriedelanes synthesis was mediated by P450 [ 26 ]. On the other hand, in Aralia elata , CYP716A295 and CYP716A296 were identified as the candidate genes most likely associated with oleanolic acid synthesis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To construct a phylogenetic relationship for the CYP712 gene family, homologous protein sequences were mined from genome assemblies of 14 species across the flowering plants (Dataset S1) and new transcriptomes from tobacco roots (Short Read Archive (SRA) accession number SRR7540357), Astragalus sinicus (SRA accession number SRR13286078) and Cosmos bipinnatus (SRA accession number SRR3546768-9) were assembled de novo using the TRINITY pipeline (Grabherr et al, 2011;Qin et al, 2020). We also included available sequences from Bupleurum chinense and Aralia elata (Araliaceae) as representatives of the Apiales order and the putative friedelin C-29 oxidase sequence from Maytenus ilicifolius (Sui et al, 2011;Bicalho et al, 2019;Cheng et al, 2020). Some genes of Kingdonia uniflora (KAF6168288), Nyssa sinensis (KAA8520263) and Trifolium pratense (Tp57577_TGAC_v2_mRNA4964) were manually re-annotated based on homology with other known Ó 2022 The Authors New Phytologist Ó 2022 New Phytologist Foundation.…”
Section: Phylogenetic Analysismentioning
confidence: 99%